KEDUDUKAN KUASA MUTLAK DALAM PERALIHAN HAK ATAS TANAH OLEH NOTARIS - Rio Yuliandana (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT       In the case of validity of a treaty, the absolute requirement that must exist in the power of attorney agreement is the agreement of the parties to enter into a power of attorney agreement, in this case the role of the Notary in performing his / her duty is obliged to provide complete and clear illumination of the consequences the law of each agreement made, and in terms of providing services and services to the parties as far as possible to avoid the occurrence of disputes in the future in order to create a legal certainty, especially in the field of land in accordance with applicable government regulations.The absolute power is what is meant in the Second Dictum of a of the Instruction of the Minister of Home Affairs Number 14 of 1982 namely:   "The Absolute Power which in the First Dictum is a power which in it contains an irrevocable element by the authorizer".        The absolute prohibition of power contained in the Instruction of the Minister of Home Affairs Number 14 of 1982 concerning the Prohibition of the Absolute Use of Proxy of the Marketer of Land Rights, where it is a power which in it contains irrevocable elements and essentially the transfer of rights to the land which gives authority to the authorized party to control and use the land and to perform any legal act which according to law can only be done by the right holder.Absolute power is what is meant in the Second Dictum of the Instruction of the Minister of Home Affairs No. 14 of 1982 namely: "The Absolute Power in the First Dictum is a force in which it contains elements that can not be annulled by the authority".         The absolute prohibition of power contained in the Instruction of the Minister of Home Affairs Number 14 of 1982 concerning the Prohibition of the Use of a Power of Attorney for Marketers of Rights to Land, which constitutes a force which contains irrevocable elements and is essentially a transfer of rights on land authorizing the authorities to control and use the land and take legal action which by law can only be done by the rights holder.  Keywords: Absolute Power, Land Rights Transfer